When the Money Runs Out : Do Cash Transfers Have Sustained Effects on Human Capital Accumulation? - Baird, Sarah; McIntosh, Craig; Ozler, Berk (World Bank, Washington, DC, 2016)
This study examines the medium-term effects of a two-year cash transfer program targeted to adolescent girls and young women. Significant declines in HIV prevalence, teen pregnancy, and early marriage among recipients of unconditional cash transfers (UCTs) during the program evaporated quickly two years after the cessation of transfers. However, children born to UCT beneficiaries during the program had significantly higher height-for-age z-scores at follow-up. On the other hand, conditional cash transfers (CCTs) offered to out-of-school females at baseline produced a large increase in educational attainment and a sustained reduction in the total number of births, but caused no gains in health, labor market outcomes, or empowerment. The findings point to both the promise and the limitations of cash transfer programs for sustained gains in welfare among young women.